A conflict of choice: How consumers choose where to go for dinner. (February 2015) - Jung, Jae Man; Sydnor, Sandra; Lee, Seul Ki; Almanza, Barbara
Abstract: Studies concerning consumers' decision-making regarding a restaurant choice commonly cite food quality, service quality, and price as important determinants. Less research has focused on how consumers are willing to trade off gains and losses from respective foodservice attributes. Also, extant literature does not account for consumers who use a non-compensatory decision-making strategy. The present study examined consumers' choices of casual restaurants using a simulation where trade-offs were inevitable. By utilizing a choice experiment, the researchers found that food quality is the most important attribute in restaurant choice, consistent with the literature reviewed. Good service quality, however, does not increase choice likelihood while poor service quality significantly reduces it. Most importantly, we determined a considerable percentage (24.57%) of respondents do not trade off food quality for better service or a lower price. Findings of the study are discussed with implications for practitioners.